Conversion areas as a catalyst of urban development - Kamalova, Klavdiia; Logunova, Elena; Kukina, Irina (project baikal, 2023)
The transformation of industrial conversion territories plays an important role in the strategy of the urban sustainable development. Rationality, efficiency and connectivity are becoming the main characteristics of the modern urban space. The formative factors of transformation are: the urban context, the area of the reconstructed plot and the presence of heritage. The main results are an increase of the urban comfort, effectiveness of the inner-city land use, as well as economic and social well-being.